2006
DOI: 10.1158/1055-9965.epi-06-0436
|View full text |Cite
|
Sign up to set email alerts
|

Higher Methylation Levels in Gastric Mucosae Significantly Correlate with Higher Risk of Gastric Cancers

Abstract: Background: Helicobacter pylori infection potently induces methylation of CpG islands in gastric mucosae, which is considered to decrease to a certain level after active H. pylori infection discontinues. Noncancerous gastric mucosae of H. pylori -negative cases with a gastric cancer had higher methylation levels than those of H. pylori -negative healthy individuals. Here, using cases with multiple gastric cancers, we analyzed whether the higher methylation levels correlated with the higher risk of gastric canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
144
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 161 publications
(152 citation statements)
references
References 26 publications
6
144
0
1
Order By: Relevance
“…It is estimated that patients with severe gastric mucosal atrophy have high methylation levels because of long-term H. pylori infection and chronic inflammation. Additionally, we reported that patients with multiple gastric cancers had significantly higher methylation levels than those with a single gastric cancer [38]. These data indicate that severe gastric mucosal atrophy and multiple gastric cancers before successful H. pylori eradication are risk factors for MGC.…”
Section: Discussionmentioning
confidence: 57%
“…It is estimated that patients with severe gastric mucosal atrophy have high methylation levels because of long-term H. pylori infection and chronic inflammation. Additionally, we reported that patients with multiple gastric cancers had significantly higher methylation levels than those with a single gastric cancer [38]. These data indicate that severe gastric mucosal atrophy and multiple gastric cancers before successful H. pylori eradication are risk factors for MGC.…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies have shown that H.pylori infection could induce aberrant DNA methylation at the CpG islands, resulting in inactivations of tumor suppressor genes in gastric mucosa, and creating predisposed fields for cancerization Nakajima et al, 2006;Tsang et al, 2011). In contrast, a study reported that H.pylori infection did not induce either mRNA or protein expression of DNMT1, DNMT3a and DNMT3B in gastric mucosa directly (Nakajima et al, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…Consequently, identification of sensitive and reliable biomarkers for diffuse type gastric cancer would be highly desirable. A number of studies have shown aberrant DNA methylation in precancerous lesions, including chronic gastritis and intestinal metaplasia, and detection of such an epigenetic field defect would provide useful information for identifying individuals at high risk for developing gastric cancer (7,24,25). The majority of those studies focused on well-studied genes, such as CDH1 and p16 (26,27), but recent advances in microarray technology have enabled us to conduct a genome-wide analysis of CpG island methylation status.…”
Section: Discussionmentioning
confidence: 99%